Mesoscale precipitation systems and their role in the rapid development of a monsoon depression over the Bay of Bengal. (2nd December 2019) - Fujinami, Hatsuki; Hirata, Hidetaka; Kato, Masaya; Tsuboki, Kazuhisa
Abstract: The structure of mesoscale precipitation within monsoon depressions is still not as well‐known as the synoptic‐scale composite cloud and precipitation structure. Here, using observational data from multi‐satellite sensors and a cloud‐resolving regional model, we investigate the three‐dimensional structure of mesoscale precipitation systems in the different stages of the life cycle of a monsoon depression. Effects of latent heating from the precipitation systems and the Bay of Bengal (BoB) on the development of the monsoon depression are also evaluated in sensitivity experiments with the model. A typical monsoon depression developed on 17 August 2016 over the BoB. In the rapid development phase, satellite observations reveal mesoscale convective systems with deep convective precipitation cells and stratiform precipitation near the head of the BoB. Extremely deep and intense convective cells appear along a ring‐like rain band when a closed cyclonic circulation becomes obvious around the northernmost part of the BoB. The deep convection appears frequently, particularly along the western‐to‐southwestern side of the low, a convergence‐prone area between northerlies with air masses of large convective available potential energy (CAPE) that makes up the western–southwestern part of the closed cyclonic circulation, and strong monsoon westerlies with relatively stable air masses to the south of the low. Sensitivity experiments reveal that both cloud/precipitation processes and evaporation from the BoB are essential for the rapid development of the monsoon depression over the BoB. Evaporation from the BoB adds a large amount of moisture to the atmospheric boundary layer near the low. Southwesterlies and southerlies on the eastern side of the low draw in warm, humid boundary‐layer air to the closed cyclonic circulation, which maintains a large‐CAPE environment in the low and enhances deep convection. A possible positive feedback process including moist convection that leads to the rapid intensification of monsoon depressions over the BoB is discussed. Abstract : The structure of mesoscale precipitation within monsoon depressions is still not as well‐ known as the synoptic‐scale composite cloud and precipitation structure. Here, using observational data from multi‐satellite sensors and a cloud‐resolving regional model, we investigate the three‐dimensional structure of mesoscale precipitation systems in the different stages of the life cycle of a monsoon depression. Effects of latent heating from the precipitation systems and from the Bay of Bengal on the development of the monsoon depression are also evaluated in sensitivity experiments with the model.